Adhesion characteristics of Staphylococcus aureus bacterial cells on funnel-shaped palladium–cobalt alloy nanostructures. Issue 7 (2nd May 2016) - Gu, Junhua; Chen, Paul Z.; Seo, Brandon B.; Jardin, Joanna M.; Verma, Mohit S.; Jahed, Zeinab; Mofrad, Mohammad R. K.; Gu, Frank X.; Tsui, Ting Y.
ABSTRACT: The adhesion properties of Staphylococcus aureus on palladium–cobalt (Pd–Co) alloy nanostructures with various cross-sectional geometries have been characterised. They include solid core, hollow, c-shaped, and x-shaped pillars. These pillars have unique funnel-shaped geometric features on the top surfaces with average included angles between ∼142 o and ∼149 o . The success rates of cell attachment on these pillar tops were quantified by using field emission scanning electron microscopy techniques. Results show the Staphylococcus aureus attachment rates of Pd–Co solid core, hollow, and x-shaped pillars are statistically indistinguishable with success rate up to 82%. X-shaped pillars have the lowest attachment rate among the four geometries of 46 ± 5%.